Atraumatic Left Distal Radial Artery Aneurysm - Joseph Maalouly; Dany Aouad; Elias Saidy; Antonios Tawk; Georges Baaklini; Chawki Cortbawi (Case Reports in Orthopedics)
Distal radial artery aneurysms are an uncommon pathological entity in the field of surgery. Moreover, distal radial artery aneurysms of idiopathic etiology are even rarer. Herein, we present a rare case of idiopathic/atraumatic left radial artery aneurysm. A 73-year-old female patient presented with a chief complaint of a pulsatile mass located on her left wrist. Radiological imaging showed the presence of a distal radial artery aneurysm which was successfully surgically excised with subsequent ligation of the radial artery. Some of the etiologies and operative management of distal radial artery aneurysm in the anatomical snuffbox to what is in accordance with the literature are discussed. Distal radial artery aneurysms are rare. Hence, their misdiagnosis may lead to wrongful management and increase in morbidity. The appropriate management of distal radial aneurysm is almost always surgical.